The Microbiome of the Cosmopolitan Diatom Leptocylindrus Reveals Significant Spatial and Temporal Variability - Ajani, Penelope A.; Kahlke, Tim; Siboni, Nachshon; Carney, Rick; Murray, Shauna A.; Seymour, Justin R. (Frontiers in Microbiology, 2018)
The ecological interactions between phytoplankton and marine bacteria have important implications for the productivity and biogeochemistry of ocean ecosystems. In this study we characterized the microbial assemblages associated with multiple isolates of the ecologically important diatom Leptocylindrus using amplicon sequencing of the 16S rRNA gene, to examine levels of conservation of the microbiome across closely related species or strains. We also assessed if the microbiome structure of a given diatom strain was dependent on the location from which it was isolated and if the microbiome of cultured isolates significantly changed overtime from the seawater in which they were isolated. The bacterial assemblages from 36 strains belonging to three species (L. danicus, L. convexus and L. aporus) isolated from six locations spanning >1000 km of south east Australian coastline over one year, were dominated by the Rhodobacteraceae (~60 %) and the Flavobacteriaceae (~10%). Across all strains, only one ‘core OTU' (Roseovarius sp.) was identified across all samples. We observed no significant differences in bacterial community composition within replicates from a given strain or between diatom species. Significant differences in microbiome structure were, however, observed between diatom strains collected at different sampling times and from differing locations. Moreover, while bacterial communities under domestication varied from the seawater in which they were isolated, they remained specific to the location/month of origin, that is, different regions and time points harboured distinct bacterial communities. Our study delivers new knowledge in relation to diatom-bacterial associations, revealing that the location/time from which a diatom is isolated plays an important role in shaping its microbiome.